Determination of an organophosphate pesticide using antibody immobilised hybrid nanocomposites. Issue 11 (2nd September 2021) - Kaur, Navpreet; Bhatnagar, Archana; Bhalla, Aman; Prabhakar, Nirmal
ABSTRACT: In this study, the malathion specific polyclonal antibodies (Abs) were raised for the fabrication of an electrochemical immunosensor using poly (3, 4-ethylenedioxythiophene) (PEDOT) and carboxylated multiwalled carbon nanotubes (c-MWCNTs) nanocomposites. The conjugation of hapten (malathion diacid) with bovine serum albumin (BSA) through N-hydroxysuccinimide (NHS) ester method was optimised for the generation of Abs. New Zealand White (NZW) male rabbits were immunised subcutaneously for the development of Abs followed by characterisation and purification. The purified Abs were covalently immobilised on nanocomposites deposited onto fluorine tin oxide (FTO). Based on immunoreaction between malathion and anti-malathion Abs, the DPV peak current was found to be inversely proportional to increase in malathion concentration. The detection limit was 1.1 fM under all the optimised experimental parameters. The immunosensor was found to be specific as low current response was observed for malathion only in comparison to other interferents. Malathion recoveries from the spiked sample were found to be superior via immunosensor than HPLC.